2008
DOI: 10.1529/biophysj.107.121160
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Local Membrane Curvature Induction by N-BAR Domains as Revealed by Molecular Dynamics Simulations

Abstract: N-BAR domains are protein modules that bind to and induce curvature in membranes via a charged concave surface and N-terminal amphipathic helices. Recently, molecular dynamics simulations have demonstrated that the N-BAR domain can induce a strong local curvature that matches the curvature of the BAR domain surface facing the bilayer. Here we present further molecular dynamics simulations that examine in greater detail the roles of the concave surface and amphipathic helices in driving local membrane curvature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
136
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 42 publications
6
136
0
Order By: Relevance
“…Second, we showed that the membrane lipid composition has a distinct impact on the liposome-reshaping and BAX-activating functions of Bif-1 N-BAR. The finding that several different anionic lipids providing the same net negative charge to the membrane similarly affect the ability of Bif-1 N-BAR to induce intervesicular lipid mixing and to increase liposome size is consistent with the view that electrostatic interactions between positively charged residues localized in the concave surface of this module and negatively charged phospholipid headgroups is a major factor driving liposome morphological rearrangements, as previously proposed for N-BAR domains of other proteins (15,16,20,21,23). In contrast, an electrostatic effect alone does not explain the requirement of CL for the potentiation of BAX-permeabilizing function elicited by Bif-1 N-BAR, in accord with previous studies indicating that other properties of CL account for its specific role in functional BAX activation (30,31,45,46).…”
Section: Discussionsupporting
confidence: 88%
“…Second, we showed that the membrane lipid composition has a distinct impact on the liposome-reshaping and BAX-activating functions of Bif-1 N-BAR. The finding that several different anionic lipids providing the same net negative charge to the membrane similarly affect the ability of Bif-1 N-BAR to induce intervesicular lipid mixing and to increase liposome size is consistent with the view that electrostatic interactions between positively charged residues localized in the concave surface of this module and negatively charged phospholipid headgroups is a major factor driving liposome morphological rearrangements, as previously proposed for N-BAR domains of other proteins (15,16,20,21,23). In contrast, an electrostatic effect alone does not explain the requirement of CL for the potentiation of BAX-permeabilizing function elicited by Bif-1 N-BAR, in accord with previous studies indicating that other properties of CL account for its specific role in functional BAX activation (30,31,45,46).…”
Section: Discussionsupporting
confidence: 88%
“…As shown in Fig. 2C, the K23E/E42K mutation greatly reduced the spin-spin coupling of the spin-labeled Q9C, suggesting that Lys 23 and Glu 42 are involved in intermolecular interactions, and the aggregation of the ENTH domain on the vesicle surface is directly correlated with its vesicle-deforming activity.…”
Section: Vesicle Tubulation Activity Of Epsin 1 Enth Domain-tomentioning
confidence: 80%
“…It is generally thought that the insertion of H 0 to one leaflet of the lipid bilayer causes a discrepancy in bilayer surface area and consequently the positive curvature and membrane deformation (13). Membrane penetration by an amphiphilic ␣-helix is also postulated to be important for the membrane-deforming activity of N-BAR domains, including those from amphiphysin (14,42) and endophilin (43,44). However, it does not fully explain why the epsin 1 ENTH domain has such potent membrane-deforming activity despite not having intrinsic molecular curvature and why many other proteins with amphiphilic ␣-helices or hydrophobic loops show a much lower tendency to deform the lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 While helix insertion is expected to increase the area of one leaflet of the bilayer, it is unclear whether that increase is sufficient to generate high curvatures, given that helix density is limited by the size and coverage of the protein containing the helix. 44 Recently, continuum models 45 and molecular dynamics simulations 46 have predicted that helix insertions alone must occupy 10-25% of the membrane surface area in order to generate the curvatures found in endocytic structures. For Epsin ENTH, however, the helix insertion (~8 Å wide × 20 Å long ≈ 1.6 nm 2 ) takes up at most 10% of the ENTH domain's membrane footprint (~40 Å × 40 Å ≈ 16 nm 2 ).…”
Section: Introductionmentioning
confidence: 99%